Bluetooth-triggered alarm security system - Muhammad Fadhil, Abdul Malek (2010)
Security system nowadays become a need for houses or commercial premises and available with many modern features. This Bluetooth-triggered alarm security system comes with extra secure access and intelligent alarming. The system only can be accessed and configured by owner using Bluetooth communication via mobile phone to turn it on or off. In this project, when the alarm is triggered, an intruder alert message will be sent to the neighbor’s phone through Bluetooth communication. After the certain time, the alarm system will be triggered and by that time the neighbors have already surrounded the compound and the probability of the intruder to be caught is higher. IR sensor of the system will continuously monitor movement or present of human in the building. The Bluetooth module will sent intruder alert message as microprocessor (PIC) receive signal from IR sensor. The PIC is programmed to wait approximately seven minute before activated the siren. The alarm system status is indicated using LED’s to avoid owner accidently turned it off.